Avaliação das propriedades de transporte de massa contendo adições minerais - MENDES, Marcus Vinícius Araújo da Silva (2009)
The durability of reinforced concrete structures is damaged by the degrading action of the penetration of substances in the form of gases, vapors and liquids through the pores and cracks. It is known that water both in its pure form or containing dissolved ions such as chloride, sulphate, carbon dioxide or oxygen ions, can compromise the durability of concrete structures. In reinforced concrete structures at the marine environment, for example, the towers of wind power plants, this degradation can be more intense and accelerated. Thus, in the present study were analyzed concretes with different mineral additions (silica fume, blast furnace slag) and water / binder ratios (0.35, 0.45 and 0.55), with the objective to verify if the inside and cover thickness of concrete have some effect on the mechanisms of transport and also the effect of carbonation (only for concrete with w/b equal to 0.55) in the surface layer of concrete is important enough to make dificult the entry of aggressive agents in concrete. For this, the following tests to evaluate the mass transport in concrete were performed: capillary water absorption (NBR 9779:1995), water penetration under pressure (NBR 10787:1994), air permeability (method Figg), penetrability of chloride ion (ASTM C 1202: 2009), non-steadystate migration test (NT BUILD 492:1999). As a result, it was found that the mineral addition used generally provided an improvement in front of the concrete mechanisms of mass transport. In one of the properties, namely the diffusion coefficient (non-steady-state migration) of concrete with the use of silica fume and blast furnace slag, this has been reduced dramatically, around 11 times for the concrete with w/b equal to 0.55, when it is compared with concrete without mineral addition. It was observed that the inner region of concrete behaved better, in an unexpected way, than concrete cover region for some properties (capillary absorption, water penetration under pressure, penetration of chloride ions). From this conclusion, it can be said that the inner part of concrete is composed of transition zones (aggregated interface / mortar) exposed to facilitate the entry of fluids, gases and ions. About the effect of carbonation, this affected the capillary absorption and air permeability. The results led to explain that the clogging of the pores resulting from the product of carbonation (CaCO3), promoted the refinement of the pores, thus increasing capillary force and, consequently, increasing the capillary absorption. However, for air permeability this effect has damaged the passage of air through the surface layer. Finally, it is important noting that significant correlations were found among tests that evaluated the mechanisms of mass transport, namely, penetration of chloride ions and capillary absorption, diffusion coefficient (non-steady-state migration) and capillary absorption, permeability air and water penetration under pressure, penetration of chloride ions and the diffusion coefficient.